2017
DOI: 10.22219/jibe.vol1.no02.71-82
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Innovation Roles of Pesantren Business Incubator in Pondok Pesantren Sunan Drajat

Abstract: Business Incubator is one of PPSD's (Pondok Pesantren Sunan Drajat) sub-units that supports their own economy independency. PPSD have existed as an important part of education, social and especially economic institution for Muslim community in East Java. Each year, Muslim intellectuals graduate from PPDS as Santri graduates, and mostly work, not only as religion teachers, but also as entrepreneurs, back in their hometown. The phenomenon of Santri Entrepreneurs appears to be the main inspiration for Business In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
1
2
0
1
Order By: Relevance
“…With respect to the above, the present study shall be in line with Mustari (2010) and Ahwarumi and Sawarjuwono (2017) who explained the entrepreneurship was among a Pesantren's initiatives in empowering a rural region. Further, as the Pesantren Nurul 'Amal is legally recognised under the form of yayasan, thus, the current evidences may further relate to Syahyuti (1999), who explained an institutionalised Pesantren has an advanced economics vision.…”
Section: Theory Of Led and The Pesantren's Role In Promoting Itsupporting
confidence: 71%
See 2 more Smart Citations
“…With respect to the above, the present study shall be in line with Mustari (2010) and Ahwarumi and Sawarjuwono (2017) who explained the entrepreneurship was among a Pesantren's initiatives in empowering a rural region. Further, as the Pesantren Nurul 'Amal is legally recognised under the form of yayasan, thus, the current evidences may further relate to Syahyuti (1999), who explained an institutionalised Pesantren has an advanced economics vision.…”
Section: Theory Of Led and The Pesantren's Role In Promoting Itsupporting
confidence: 71%
“…In Indonesia, a contribution of Pesantren for local community can be found in Ahwarumi and Sawarjuwono (2017), Mustari (2010) and Syahyuti (1999). In this, Syahyuti (1999) studied an economic aspect of a traditional and an institutionalised Pesantren and found that a modern Pesantren registered under the form of a yayasan (legal recognition) had the better economic vision.…”
Section: Pesantren and Muslim Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…Fenomena yang menarik adalah sebagian besar lulusan Santri ini tidak hanya bekerja sebagai guru agama, tetapi juga sebagai wiraswasta, dan ini terjadi secara alamiah secara acak. Para santri lulusan ini juga dikenal sebagai agen anti kemiskinan di lingkungannya 1 . Titik tolaknya adalah integrasi penguasaan ilmu agama, sosial, dan ekonomi sebagai konsep holistik Pesantren Modern yang mengacu pada konsep dasar kemandirian pribadi dalam Islam.…”
unclassified